Menggali makna dalam puisi: Analisis teks dan interpretasi kritis - Divani, An'Nisya Amelia; Markhamah, Markhamah (Universitas Lampung, 2024)
This article aims to analyze the critical role in interpreting poetry and how this influences the understanding of the resulting meaning, analyzing critical theories to develop a deeper meaning analysis of poetry, and finally analyzing the use of language elements to explore the deeper meaning of poetry. This research utilizes a qualitative approach with a data source in the form of a collection of meanings of poetry created by students. The data collection techniques used in this research are observation, listening, reading and note-taking techniques. The data analysis technique is to use library study techniques and will be described descriptively. The findings obtained are that there are factors that influence the understanding of meaning in poetry and the critical role such as the richness of poetry language, historical and cultural context, the poet's voice, structure and form, theme and message, personal associations, analysis of context in poetry, interactions between elements in poetry. poetry, and comparison with other poetry. Furthermore, critical theories such as feminism, deconstruction, and postcolonialism can help in carrying out deeper and more relevant analyzes of gender, language and social issues. Finally, language elements such as metaphor, symbols, and diction influence the critical interpretation process in poetry in a significant way so that they can understand the meaning of poetry more deeply.Keywords: Poetry, Text Analysis, Critical Interpretation